IMPLEMENTATION OF GROUP COUNSELING SERVICES WITH SOLUTION FOCUSED BRIEF COUNSELING MODEL TO IMPROVE CAREER SELF-EFFICACY - Ni Luh Made Wia Dwiarya Putri; Ni Wayan Suastini (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
Implementing guidance and counseling in school learning is necessary, considering that students are in adolescence. At this stage, a person experiences many physical and psychological transitions that should affect his behavior, including when preparing for career choices, clarity and expectations of future work, and career self-efficacy. Applying the Solution Focused Brief Counseling model is a form of intervention that is applied in implementing cognitive improvement in a person, which focuses on finding solutions to solve problems. This study aimed at measuring the success rate of implementing Group Counseling Services with the Solution Focused Brief Counseling (SFBC) Model to Increase Students' Career Self-Efficacy. This study used a class action research method with eight students. The research was conducted through 2 cycles, beginning with the stages of planning, implementing actions, observing, and reflecting on each cycle. The tools used were observational tools to measure professional self-efficacy. Data analysis was carried out qualitatively by describing the facts collected and presented in descriptions. The result of this study is an increase in career self-efficacy in students after being given group counseling services with the SFBC model. Based on the results of the implementation of classroom action research that has been carried out, it is hoped that in the future, counseling teachers will become one of the alternative methods of implementing counseling in schools.